The Influence of Inquiry Learning Strategy and Critical Thinking Ability on the Results of Islamic Education Learning at SMA Negeri 2 Tanjung Morawa, Deli Serdang District - Abd. Mukti; Afrahul Fadhila Daulai; Oktrigana Wirian (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The objectives of this study were: (1) to determine the learning outcomes of Islamic Education students who were taught with inquiry strategy were higher than the learning outcomes of students taught by conventional learning; (2) to find out the learning outcomes of Islamic Education students who have higher critical thinking skills than students who have low critical thinking skills, and; (3) to determine the interaction between learning strategies and critical thinking skills on the learning outcomes of Islamic Education. The research method is a quasi experiment. The study design was a two-factorial analysis of variance. The research instruments were questionnaires and tests. The data analysis technique used was analysis of variance at α 0.05. The findings of the study show: (1) the average learning outcomes of Islamic Education students who are taught with Inquiry learning strategies are higher than the average learning outcomes of Islamic Education students taught with conventional learning, (2) the average educational learning outcomes Islamic students with high critical thinking skills are higher than the average learning outcomes of students with low critical thinking skills, and (3) there is an interaction between learning strategies and critical thinking skills where students with high critical thinking skills are appropriately taught using Inquiry learning strategies can be seen that on average the learning outcomes of Islamic Education are higher.